Awareness and Pattern of Utilizing Family Planning Methods in Married Women visiting at Janaki Medical College Teaching Hospital - Sushma Deo; Ragni Sinha; Lokeshwar Chaurasia; Pankaj Pratap Deo (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives: Family planning (FP) means a way of thinking, perceiving and utilizing which is accepted voluntarily upon the bases of attitude, knowledge, and important decisions by couples. This study was done to assess level of awareness and pattern of utilizing family planning methods among married women aged 20 to 45 years of reproductive age visiting at Janaki Medical College teaching Hospital, Ramdiaya. Materials and Methods: A cross-sectional study was conducted from January 2023 to July 2023 at the department of obstetrics and gynecology of Janaki Medical College and Teaching Hospital, Ramdaiya, Dhanusha, Nepal. One hundred forty three (n=143) women of reproductive age, were interviewed by using a pre-tested semi structured questionnaire. After taking informed written consent, socio-demographic characteristics, knowledge, attitude and pattern of using family planning methods were recorded. The data was analyzed by using SPSS version 21. Results: Majority (55.94%) of respondents were aware about the different contraceptive methods, and 46.85% of the respondents were using contraceptive methods at the time of our study. 16.08% were using oral contraceptives followed by condoms in 13.98%, tubectomy by 9.09%, vasectomy by 3.49%, traditional methods by 2.09 %, intrauterine device by 1.39% and injectable by 0.69%. The use of contraceptive methods increased with increasing age, number of living children and level of education. Conclusion: Average number of women were aware about the contraceptive methods but the practice of contraception and utilization of family planning services were low. A gap was found between knowledge and implementation of contraceptive methods in the study population. This shows the need for more informative awareness campaigns for promoting contraceptive utilization.